2012
DOI: 10.3324/haematol.2011.048421
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter validation of a reproducible flow cytometric score for the diagnosis of low-grade myelodysplastic syndromes: results of a European LeukemiaNET study

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe current World Health Organization classification of myelodysplastic syndromes is based on morphological evaluation of bone marrow dysplasia. In clinical practice, the reproducibility of the recognition of dysplasia is usually poor especially in cases that lack specific markers such as ring sideroblasts and clonal cytogenetic abnormalities. Design and MethodsWe aimed to develop and validate a flow cytometric score for the diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
151
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(180 citation statements)
references
References 29 publications
20
151
2
7
Order By: Relevance
“…As has been shown previously by others,26 phenotypic changes in maturing myelomonocytic cells in patients undergoing various therapies are less reliable for diagnosis of MDS or MDS/MPN by FCI than assessment of myeloid progenitors. In this study the FCI assay was designed to analyse CD34+ myeloblasts only, an approach similar to our AML MRD assay 16.…”
Section: Discussionmentioning
confidence: 72%
“…As has been shown previously by others,26 phenotypic changes in maturing myelomonocytic cells in patients undergoing various therapies are less reliable for diagnosis of MDS or MDS/MPN by FCI than assessment of myeloid progenitors. In this study the FCI assay was designed to analyse CD34+ myeloblasts only, an approach similar to our AML MRD assay 16.…”
Section: Discussionmentioning
confidence: 72%
“…These factors can be assayed with only forward scatter, side scatter, CD45, CD13, and CD33 parameters required. The FCM-score was shown to be both sensitive and specific for diagnosis of the often difficult to diagnose low-grade MDS cases and provided additive prognostic power to the IPSS-R (47, 48). Another study showed that the number of CD34+/CD13+ cells added prognostic value to the IPSS-R (37).…”
Section: Current Mds Prognostic Scoring Systems and Risk Modelsmentioning
confidence: 99%
“…Moreover, a FC score may help to distinguish MDS from other nonmalignant reactive or secondary cytopenias,42,43 and support the diagnosis of IDUS,24 which may represent a pre-phase of MDS. The Ogata score, based on a 4-color analysis of 13 antigens, has shown a sensitivity of 70% and a specificity of 92% in the whole MDS group 43. For RCUD, the sensitivity was 62%, and a specificity reaching 97% in distinguishing MDS from immune cytopenias 43.…”
Section: Diagnostic Tools For the Diagnosis Of Rt And Rnmentioning
confidence: 99%
“…The Ogata score, based on a 4-color analysis of 13 antigens, has shown a sensitivity of 70% and a specificity of 92% in the whole MDS group 43. For RCUD, the sensitivity was 62%, and a specificity reaching 97% in distinguishing MDS from immune cytopenias 43. Additionally, a FC score is likely to bring prognostic information in MDS even when the blast count is below 5%, with a high correlation with transfusion dependency, cytogenetics, and the IPSS score 44.…”
Section: Diagnostic Tools For the Diagnosis Of Rt And Rnmentioning
confidence: 99%